Capacity Building in the Tourism Sector a few lessons for government - Kalacas, Maria Rellie B. (Ashland Society Publishing, 2021)
"The book Capacity Building in the Tourism Sector: A Few Lessons for Government emphasizes on the role of governments around the world in improving the conditions and environment for tourism. It emphasizes on the need for skilling up the local people, building proper infrastructure, providing primary and basic education to the locals, enhancing the trade market and local craftsmen and maintenance of the tourist spots and various other things that aim at capacity building for tourism. It explains the manner in which each of these things can enhance the tourism sector and help in reaping better returns."
Chapter 1 Introduction to Tourism -- 1.1. Introduction -- 1.2. Tourism -- 1.3. Types of Tourism -- 1.4. Global Overview -- 1.5. Economic Impacts of Tourism -- 1.6. Socio-Cultural Impacts of Tourism -- 1.7. Environmental Impact of Tourism -- 1.8. Sustainable Tourism -- 1.9. Conclusion -- Reference -- Chapter 2 An Outline On Capacity Building -- 2.1. Introduction -- 2.2. Historical Perspective -- 2.3. Conceptual Framework Underpinning Capacity Building -- 2.4. How Capacity Building or Development Is Understood In The United Nations Development System -- 2.5. Investing In Future Strength And Capability -- 2.6. The Five Steps of The Capacity Development Cycle -- 2.7. Key Recommendations To Help Build Capacity In Organizations -- 2.8. Importance of Capacity Building To Future Success -- 2.9. Challenges With Capacity Building -- 2.10. Conclusion -- References -- Chapter 3 Relevance of Capacity Building In Tourism Sector -- 3.1. Introduction -- 3.2. Capacity Building And Different Dimensions Of Community -- 3.3. Distribution Of Power In A Community -- 3.4. Community Capacity Building (CCB) For Sustainable Tourism Development -- 3.5. Community Capacity Building (CCB) Through Tourism In Developing Countries -- 3.6. Factors Affecting The Involvement Of Capacity Building In Tourism Activities -- 3.7. Tourism For Capacity Building -- 3.8. Conclusion -- References -- Chapter 4 Community Capacity Building -- 4.1. Introduction -- 4.2. Fundamental Characteristics Of Community Capacity -- 4.3. How Is Community Capacity Built? -- 4.4. Principle Of Community Capacity Building (CCB) -- 4.5. Philosophical Context For Community Capacity Building (CCB) -- 4.6. Implementing Community Capacity Building (CCB) -- 4.7. Measuring Community Capacity Building (CCB): A Basic Vocabulary -- 4.8. Importance Of Community Capacity Building (CCB) -- 4.9. Conflict Resolution Capacity -- 4.10. Critique Of Community Capacity Building (CCB) -- 4.11. Conclusion -- References -- Chapter 5 Methods Of Capacity Building In Tourism Industry -- 5.1. Introduction -- 5.2. Emerging Areas Of Tourism-Need For New Skills -- 5.3. Challenges That Affect The Development Of Tourism -- 5.4. Importance And Need For Community Capacity Building (CCB) -- 5.5. Steps In Capacity Building -- 5.6. Manpower Management In Tourism And Capacity Building -- 5.7. Methods Of Capacity Building In Tourism -- 5.8. Tourism Training Strategy -- 5.9. Important Aspects Of Tourism Training Strategy -- 5.10. Enhancing Skills To Increase Employability -- 5.11. Levels Of Training -- 5.12. Conclusion -- References -- Chapter 6 Challenges Of Capacity Building In Tourism Industry -- 6.1. Capacity Building In Tourism And Its Challenges -- 6.2. Problems In Capacity Building Of Sustainable Tourism Development -- 6.3. The Growth Paradox: Can Tourism Ever Be Sustainable?
Keywords: Tourism policy; Tourism development; Community-based tourism